2007
DOI: 10.1186/1742-9994-4-16
|View full text |Cite
|
Sign up to set email alerts
|

A novel and ancient group of type I keratins with members in bichir, sturgeon and gar

Abstract: Abstract1. Background: Vertebrate epithelial cells typically express a specific set of keratins. In teleosts, keratins are also present in a variety of mesenchymal cells, which usually express vimentin. Significantly, our previous studies revealed that virtually all known teleost keratins evolved independently from those present in terrestrial vertebrates. To further elucidate the evolutionary scenario that led to the large variety of keratins and their complex expression patterns in present day teleosts, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…In addition to α‐ and β‐keratins forming intracellular keratin filaments as part of the cytoskeleton, extracellular keratins (i.e. thread keratins TKα and TKβ) are produced and secreted by specialized epidermal cells in hagfishes, lampreys, teleost fishes and amphibians (Schaffeld & Schultess, 2006; Schaffeld et al 2007). The nucleotide sequence of the genes encoding these thread keratins, as well as the amino acid sequence deduced from the mRNA, supports a close relationship of the extracellular thread keratins to the intracellular α‐keratins.…”
Section: Keratins Characteristic Of Certain Types Of Epitheliamentioning
confidence: 99%
“…In addition to α‐ and β‐keratins forming intracellular keratin filaments as part of the cytoskeleton, extracellular keratins (i.e. thread keratins TKα and TKβ) are produced and secreted by specialized epidermal cells in hagfishes, lampreys, teleost fishes and amphibians (Schaffeld & Schultess, 2006; Schaffeld et al 2007). The nucleotide sequence of the genes encoding these thread keratins, as well as the amino acid sequence deduced from the mRNA, supports a close relationship of the extracellular thread keratins to the intracellular α‐keratins.…”
Section: Keratins Characteristic Of Certain Types Of Epitheliamentioning
confidence: 99%
“…In the same manner as the FGK gene, the XK81 gene is duplicated in X. laevis (Miyatani et al, 1986). Over 20 type I keratin genes have thus far been identified in X. laevis (Schaffeld et al, 2007), while only 14 type I keratin genes are found in X. tropicalis with a diploid genome (the Ensembl database based on JGI Xenopus tropicalis genome assembly Ver. 4.1).…”
Section: Fgk and Other Type I Keratin Genes In Xenopusmentioning
confidence: 94%
“…These keratin genes flank the SMARCE1 (SWI/SNF-related matrix-associated actin-dependent regulator of chromatin, subfamily e, member 1) and SUI1 (translation initiation factor, SUI1) genes, similar to the case for mammals and birds (Zimek and Weber, 2005). Although the syntenic relationships among the type I keratin genes, therefore, appear to be conserved between mammals and amphibians, there are no orthologous amino acid sequences between the mammalian and Xenopus type I keratin subtypes (Schaffeld et al, 2007). These data suggest that the amphibian keratin genes specified and diverged during evolution.…”
Section: Fgk and Other Type I Keratin Genes In Xenopusmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated scales and skull bones, attributed to the Polypterus species, testify the presence of the genus in African freshwaters since the Eocene, but the monophyletic family of the Polypteridae includes actually only two holocenic living genera: Polypterus, with 16 recognized species, and the monotypic genus Erpetoichthys, with the unique most derived species Erpetoichthys calabaricus, the only living in the coastal areas of the African estuaries (Gayet et al, 2002;Schafer, 2004;Claeson et al, 2007). Assigned in the past to a different group of bony fish, Polypteriformes are currently included into the Cladistia, the most basal Actinopterygians group Meyer, 1996, 2001;Zardoya et al, 1998;Cao et al, 1998;Rasmussen and Arnason, 1999a,b;Arnason et al, 2001;Venkatesh et al, 1999Venkatesh et al, , 2001Daget et al, 2001;Britz and Johnson, 2003;Britz and Bartsch, 2003;Hoegg et al, 2004;Kikugawa et al, 2004;Gardiner et al, 2005;Chiu et al, 2006;Schaffeld et al, 2007), the sister group of Marine Genomics 4 (2011) 25-31 the Actinopteri (Chondrostei + Neopterygii), but the interrelationships among polypterids extant species have yet to be clarified (Claeson et al, 2007). Data set regarding the karyology in these species are poor (Denton and Howell, 1973;Capanna and Cataudella, 1973;Urushido et al, 1977;Cataudella et al, 1978;Vervoort, 1980a,b;Morescalchi et al, 2007Morescalchi et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%